A Socialization on the Insights of TOEFL to Students of SMK GKPI 2 Pematang Siantar - Sitompul, Mega Silvia; Siagian, Dian Melati; Siahaan, Entika Cintami; Simangunsong, Rahelian Gratia; Carolina, Carolina; Herman, Herman; Sitanggang, Anita; Purba, Ridwin (Indra Institute Research & Publication, 2023)
This community service aims to introduce and provide new knowledge, understanding and insights to the students at SMK GKPI 2 Pematang Siantar about TOEFL. There were 25 participants in the socialization activity, consisting of students from class in the lecture session, the researchers gave the participants the opportunity to ask question about the material that had been explained and provided. The lecture session is a session where the researcher provides material regarding TOEFL, namely: understanding TOEFL, types of TOEFL, benefits and uses of TOEFL, how to access free TOEFL practice, TOEFL test costs and places as well as tips and tricks for doing TOEFL test questions quickly and easily via PowerPoint. Meanwhile, the discussion session is a question and answer session between participants and researchers regarding the material that has been presented during the socialization activity. The result obtained from the socialization activity are: (1) participants gain new knowledge and insight about the importance of TOEFL, such as what is TOEFL; types of TOEFL; benefits and use of TOEFL; TOEFL test and location; tips and trick for answer TOEFL question quickly and correctly, (2) the participants were very enthusiastic to take part in this socialization activity.